2020
DOI: 10.1186/s12887-020-02243-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the child-doctor relationship in research participation: a qualitative study

Abstract: Background: Children have reported that one reason for participating in research is to help their doctor. This is potentially harmful if associated with coercive consent but might be beneficial for recruitment. We aimed to explore children's perceptions of the child-doctor relationship in research. Methods: This is a multicenter qualitative study with semi structured interviews performed between 2010 and 2011 (United Kingdom) and 2017-2019 (the Netherlands). Interviews took place nationwide at children's homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Literature on clinical trial adherence in the paediatric age group is scarce. A qualitative study by Luchtenberg et al [ 45 ] , which explored children’s perceptions of the child-doctor relationship in research participation, found that familiarity and a trusting relationship led to a feeling of mutuality and enhanced children’s confidence, improved recruitment, and engagement throughout the research process. When their participants did not have a prior relationship with a researcher, as is the case with the PIPPA Tamariki trial, participants depended more on family support when introduced to research [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature on clinical trial adherence in the paediatric age group is scarce. A qualitative study by Luchtenberg et al [ 45 ] , which explored children’s perceptions of the child-doctor relationship in research participation, found that familiarity and a trusting relationship led to a feeling of mutuality and enhanced children’s confidence, improved recruitment, and engagement throughout the research process. When their participants did not have a prior relationship with a researcher, as is the case with the PIPPA Tamariki trial, participants depended more on family support when introduced to research [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study by Luchtenberg et al [ 45 ] , which explored children’s perceptions of the child-doctor relationship in research participation, found that familiarity and a trusting relationship led to a feeling of mutuality and enhanced children’s confidence, improved recruitment, and engagement throughout the research process. When their participants did not have a prior relationship with a researcher, as is the case with the PIPPA Tamariki trial, participants depended more on family support when introduced to research [ 45 ]. Several authors have also emphasised the importance of establishing participant trust [ 20 ], raising awareness [ 12 , 13 , 20 ], and involving family members or other social support networks [ 12 , 20 ] to promote involvement in all aspects of the research process, including intervention adherence [ 12 , 13 ], as well as participant recruitment [ 17 19 ] and retention [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the diagnosis involves a child, there is the emergence of a doctor-child-guardian trinomial relationship [ 8 ]. In addition to the aforementioned aspects, trust and familiarity are essential for child involvement [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the diagnosis involves a child, there is the emergence of a doctor-child-guardian trinomial relationship [ 8 ]. In addition to the aforementioned aspects, trust and familiarity are essential for child involvement [ 8 ]. Cognitive maturity does not always match the chronological one and, therefore, the ability to consent must be ascertained in agreement with the possibility of abstraction and understanding of information [ 9 ].…”
Section: Introductionmentioning
confidence: 99%